PELAYANAN FISIOTERAPI PADA CEDERA FASE AKUT DALAM KEGIATAN BIMA NATA CUP DI DESA PELAGA - I Putu Prisa Jaya; I.A Pascha Paramurthi; I Made Dhita Prianthara; Komang Tri Adi Suparwati; Ida Ayu Astiti Suadnyana; I Putu Astrawan; I Gusti Ayu Sri Wahyuni Novianti (Jurnal Abdi Insani, 2022)
Football is a group sport that is popular all over the world that has a high risk of falling and impacting so that it can cause injury. To avoid this, a medical team must be prepared such as doctors and physiotherapists, either prepared by the team or provided by the match organizer. Basically Physiotherapy aims to develop, maintain and restore movement and bodily function through manual manipulation, motion enhancement, functional exercises and communication at individuals and groups. This activity aims to provide the first treatment for injuries suffered by football athletes who compete in the Bima Nata Cup activities, especially in providing physiotherapy services for acute injuries. The methods used in accordance with the physiotherapy care system start from inputs: namely athletes who have suffered injuries, process: examination of athletes followed by the preparation of interventions according to the injuries experienced, outputs: athlete's recovery and outcomes: the athlete's satisfaction with the servants provided. The results of the services performed on the 15 football clubs that compete physiotherapists can help and provide treatment to athletes who have suffered injuries while competing. Based on the number of injury cases, the most cases of injuries to the ankle were 33%, injuries to the knee were 25%, injuries to the hamstring were 20%, injuries to the shoulder were 8%, injuries to the wrist were 8% and injuries to the wrist were 6%. The process carried out is in the form of a physiotherapy process which includes assessment, diagnosis, intervention and evaluation. Physiotherapy interventions carried out using the RICE method and the use of physiotherapy modalities in the form of exercise therapy. It can be concluded that there were 36 athletes who suffered injuries. And it can illustrate that the need for physiotherapy services in a football.